Guidelines for training in agroforestry - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
'Guidelines for Training in Rapid Appraisal for Agroforestry Research and Extension, by N O J Abel, M J Drinkwater, J Ingram, J Okafor and R T Prinsley, 1989, 117pp, ISBN 0 85092 337 9